Effects of vagal denervation on cerebral blood flow regulation immediately after the onset of ventricular pacing in anesthetized rats - Kei Ishii; Hidehiko Komine; Takeyuki Oba (Scientific Reports)
Abstract Cerebral blood flow (CBF) appears to be selectively distributed in vital brain regions during rapid severe hypotension caused by tachyarrhythmia. To examine the effect of cardiopulmonary vagal afferent signals on region-specific CBF regulation, we compared CBF responses 1–4 s from the onset of ventricular pacing (at 550–850 beats/min) between vagotomized and sham-operated anesthetized male Wistar rats. Laser Doppler flowmetry was used to measure CBF in nine different brain regions from the cortex to the pons. The effects of vagotomy on cerebrovascular responsiveness to 5% CO2 exposure were also examined. Vagotomized rats showed an increased baseline heart rate and a diminished decrease in mean arterial pressure (MAP) during ventricular pacing compared with the sham-operated rats. In all the brain regions, CBF responses to pacing-induced moderate (− 34 mmHg ≤ ΔMAP ≤  − 15 mmHg) and severe hypotension (− 54 mmHg ≤ ΔMAP ≤  − 35 mmHg) were comparable between the groups. Vagotomy had no effect on the cerebrovascular response time or reactivity to hypercapnia. The present findings suggest that cardiopulmonary vagal afferent signals are not essential for cerebrovascular counterregulation immediately after the onset of ventricular tachycardia.